Implementation and Control of a Magnetic Levitation System - Venghi, Luis Esteban (2016)
A magnetic levitation control system is developed in this work. The non-linear system model is linearized around the operating point. Two control loops, an inner current loop and an outer position loop are designed using the linear system obtained. The hardware implementation is described. Simulation and experimental results are shown to validate the dynamic response of proposed control.